Tetanus vaccination status in construction workers: results from an institutional surveillance campaign - Riccò, Matteo; Vezzosi, Luigi; Cella, Carlo; Pecoraro, Marco; Novembre, Giacomo; Moreo, Alessandro; Ognibeni, Enrico Maria; Schallenberg, Gert; Maranelli, Graziano (Acta Biomedica Atenei Parmensis, 2019)
Background: Since 1963 Italian law (Law 292/1963, Legislative Decree n.81/2008), defines Tetanus Vaccination (TeV) as mandatory for defined occupational categories, including Construction Workers (CWs). Materials and Methods: An institutional survey on of CWs was performed in the Autonomous Province of Trento (Oct. 2016 - Apr. 2017). Vaccination booklets/certificate were retrieved recalling: TeV status (1), and TeV settings (2), i.e. basal schedule; year of last shot, healthcare providers who performed TeV, and TeV formulate(s). Results: Data about 205 CWs were collected (mean age 40.6±10.3 years; 78.0% <50 year-old, 71.7% born in Italy). Overall, 38.5% of CW had received last vaccination shot >10 years before the survey (mean: 8.8 ± 8.2 years). The majority of boosters had been administered by Vaccination Services of the Local Health Unit (47.3%), followed by Occupational Physicians (20.0%) and General Practitioners (11.2%). In 85.9% of CWs, a monovalent formulation was used. Combined TeV were mainly reported in CW who had received last vaccination shot in Vaccination Services (96.2%; p<0.001). Conclusions: TeV coverage rates in CWs are insufficient, and vaccination shots are frequently performed with inappropriate, monovalent formulates. As only professionals from Vaccination Services systematically employ combined vaccines and particularly Tdap, our results not only stress the opportunity for promoting TeV among CWs, but also the importance of improving reception of up to date official recommendations in Occupational Physicians, General Practitioner and professionals of Emergency Departments.